Catalog of Clinical Images (Out of Print) - Charlie Goldberg (Association of American Medical Colleges, 2006)
Abstract This resource is a web-based collection of images of common and uncommon physical exam findings organized into eight categories: head-neck, eyes, thorax, upper extremities, abdomen, genital/rectal, lower extremities, and skin. The site is accessible to anyone (i.e., students, clinicians, patients) who might be interested.